The Development of Crocheting Teaching Material for Student with Hearing Impairment in SMALB - Imai Larasati; Sopingi Sopingi (Journal of ICSAR, 2018)
The goal of this research is to produce the crocheting teaching material that fit the characteristics and needs of students with hearing impairment. This research used Borg & Gall (1983) development research design. The result of material expert validation data analysis shows that mean value 71%, 94% of learning expert, 93% of media expert, and 100% of linguist. The result of performance test analysis on three students with hearing impairment shows effectiveness value 64.96. Based on expert validation data and students performance test result analysis, it can be concluded that teaching material is valid and effective to be used as reference in crocheting learning activities